PENGARUH KUALITAS LAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS PASIEN YANG DIMEDIASI KEPUASAN PASIEN DI KLINIK UTAMA ARDITA - Rampi, Chintya Natalia; Winoto Tj, Hery; Fushen, Fushen (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
This study was conducted with the aim of determining the effect of service quality and trust on patient loyalty mediated by patient satisfaction. Respondents in this study were patients who came for outpatient treatment at the Ardita Main Clinic. Hypothesis testing was conducted using quantitative research with a sample size of 200 respondents. Data collection was carried out by distributing questionnaires to respondents. The analysis in this study was carried out through Structural Equation Modeling (PLS-SEM) analysis. Based on the results of data processing and data analysis it was found that there is no direct effect of service quality on patient loyalty, no direct effect of trust on patient loyalty. There is significant effect service quality on patient satisfaction, there is a significant influence of trust on patient satisfaction, there is the effect of service quality on patient loyalty mediated by patient satisfaction, and indirectly there is a significant effect of trust on patient loyalty by mediating patient satisfaction. Utama Ardita Clinic is a clinic located in Cilangkap, with this the management can improve the health service that can increase patient satisfaction so that there is an increase in Visits to the Utama Ardita Clinic Keywords: service quality,Trust, customer satisfaction, patient loyalty